RESEARCH ON EARLY SELECTION OF SOME FAST-GROWING EUCALYPTUS UROPHYLLA FAMILIES AND GOOD TRUNK QUALITY AT THE SEED ORCHARDS IN BA VI DISTRICT, HANOI - Vu Tho, Hoang (Journal of Forestry Science and Technology, 2017)
Research on early selection of some fast-growing Eucalyptus urophylla families and good trunk quality of the seed orchards showed that, the average survival rate of 60 E. urophylla families in 2.5 year-old stage was 74.9%, and the number of families, whose survival rate are higher than the average in the whole of seed orchards, reached 53.3%. The average growth, and the annual growth rate for diameter, height and trunk volume of 60 families were 7.40 m; 7.79 m, and 16.9 dm3; and 2.97 cm; 3.11 m and 6.79 dm3 respectively. There is a significant difference in height and trunk volume between families. The family (No. 93) has the greatest value in height and trunk volume, higher than family (No. 12), which has the smallest height (smaller 1.3 times), and the family (No. 35), which has the smallest trunk volumes (smaller 2.3 times). The quality of the trunk according to single criteria does not differ between families, meanwhile the quality of synthesis (Sqc) is opposite, the family (No. 93) with the highest the quality of synthesis is 30.8; higher than the family (No. 11) with the lowest quality of synthesis, which was lower1.62 times in the same time and condition. Among the 60 families of the seed orchards, only 13 of them selected with fast growth norms (D1.3, Hfull and V), and 10 other families with the quality of synthetis criteria, exceeds level 10% compared to the whole of seed orchards, reaching 21.6% and 16.6% respectively. Out of 60 families, only 6 of them can be chosen including: family No. 93, 34, 45, 31, 15 and No. 92, exceed level 10% both for growth norms and the quality of synthesis criteria compared to the whole of seed orchards. The results of this study are the basis of the proposal of the early selection of some E. urophylla families with fast growth, good trunk quality, as well as thinning of slow growth and poor trunk quality of the seed orchards.